2018
DOI: 10.1021/acs.jcim.8b00641
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Self-Assembly Strategy for Encapsulation of an Amphipathic α-Helical Antimicrobial Peptide into the Different Polymeric and Copolymeric Nanoparticles

Abstract: Encapsulation of peptide and protein-based drugs in polymeric nanoparticles is one of the fundamental fields in controlled-release drug delivery systems. The molecular mechanisms of absorption of peptides to the polymeric nanoparticles are still unknown, and there is no precise molecular data on the encapsulation process of peptide and protein-based drugs. Herein, the self-assembly of different polymers and block copolymers with combinations of the various molecular weight of blocks and the effects of resultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 96 publications
1
25
0
Order By: Relevance
“…Our group simulated PEGylated magainin 2 and tachyplesin I interacting with lipid bilayers, showing that PEGylation reduces the binding strength between peptides and bilayer surfaces, which occurs more significantly for α-helical magainin 2 than for β-sheet tachyplesin I [81]. Recently, Jafari et al simulated PEG-encapsulated magainin 2 and found that the PEG-peptide interaction is significantly modulated by aromatic and basic residues of the peptide [82], and Souza et al simulated the insertion of PEG-encapsulated human beta-defensin-3 to lung surfactant models, showing that PEG chains promote the translocation of the peptide from gas phase to water phase [83]. Asadzadeh et al simulated GF-17 (17th-32nd residues of LL-37) interacting with chitosan, PEG, or both, showing that the peptide interacts more tightly with PEG than with chitosan ( Figure 3), leading to lower helicity in the presence of PEG [84].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Our group simulated PEGylated magainin 2 and tachyplesin I interacting with lipid bilayers, showing that PEGylation reduces the binding strength between peptides and bilayer surfaces, which occurs more significantly for α-helical magainin 2 than for β-sheet tachyplesin I [81]. Recently, Jafari et al simulated PEG-encapsulated magainin 2 and found that the PEG-peptide interaction is significantly modulated by aromatic and basic residues of the peptide [82], and Souza et al simulated the insertion of PEG-encapsulated human beta-defensin-3 to lung surfactant models, showing that PEG chains promote the translocation of the peptide from gas phase to water phase [83]. Asadzadeh et al simulated GF-17 (17th-32nd residues of LL-37) interacting with chitosan, PEG, or both, showing that the peptide interacts more tightly with PEG than with chitosan ( Figure 3), leading to lower helicity in the presence of PEG [84].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…AMPs were found to be compatible with PEG. The ligand PEG stabilizes the secondary structure of a helical peptide, a 33-residue designed coiled peptide, in which polymers with higher molecular weight increase the peptide helicity (Jafari et al, 2019) . Helicity was proved to play a crucial role on peptide specificity and biological activities.…”
Section: Antimicrobial-peptide-conjugatedmentioning
confidence: 99%
“…Increasing helicity by pairing with PEG allows AMP to increase it capabilities. Pairing AMP with PEG minimizes the effects of AMPs on healthy cells (Jafari et al, 2019). However, AMPs have some drawbacks.…”
Section: Antimicrobial-peptide-conjugatedmentioning
confidence: 99%
“…However, there are a few reports on simulated PLGA-PEG combinations, which are very common in experimental assessments due to their properties as a result of a combination of hydrophobic and hydrophilic parts. For example, Jafari et al considered the influence of PEG chains in various combinations with PLGA polymers on the stability and aggregation behavior of micelles 21 . Their results revealed that regardless of the sequence of polymers, the aggregation behavior of the micelles had no significant change.…”
Section: Introductionmentioning
confidence: 99%